If the maximum power of 5 in is (For example since ), find the value of
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First of all, the maximum power of a prime number p in n ! is given by h = i = 1 ∑ ∞ ⌊ p i n ⌋ (take note that if p i > n , then ⌊ p i n ⌋ = 0 , so this equation does have a finite value).
To show this, see that n ! = n × ( n − 1 ) × ( n − 2 ) × … × 2 × 1 , completely factorize these n numbers so that every number is expressed as the product of their prime factors, then h is actually the sum of exponents of all the p 's.
If the number of p that has the exponent a is h a , then h = h 1 + 2 h 2 + 3 h 3 + 4 h 4 + … = N 1 + N 2 + N 3 + N 4 + … where N j = i = j ∑ ∞ h i shows how many numbers from 1 to n that are divisible by p j , which is given by ⌊ p j n ⌋ .
Hence h = i = 1 ∑ ∞ N i = i = 1 ∑ ∞ ⌊ p i n ⌋
Now, n = 1 ∑ 1 1 5 3 [ k n × ( − 1 ) n + 1 ] = n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ( ⌊ 5 n ⌋ + ⌊ 5 2 n ⌋ + ⌊ 5 3 n ⌋ + ⌊ 5 4 n ⌋ ) ]
Consider n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ⌊ 5 n ⌋ ] , n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ⌊ 5 n ⌋ ] = 0 − 0 + 0 − 0 + 1 − 1 + … 5 terms − 2 + 2 − … 5 terms + … + 2 2 9 − 2 2 9 + … 5 terms 1 1 4 5 terms − 2 3 0 + 2 3 0 − 2 3 0 + 2 3 0 = 1 − 2 + 3 − 4 + 5 − … − 2 2 8 + 2 2 9 1 1 4 terms = 1 + 1 1 4 = 1 1 5
Consider n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ⌊ 5 2 n ⌋ ] , n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ⌊ 5 2 n ⌋ ] = 2 4 × 0 + 1 − 1 + … 2 5 terms − 2 + 2 − … 2 5 terms + … − 4 5 + 4 5 − … 2 5 terms 1 1 2 5 terms + 4 6 − 4 6 + 4 6 − 4 6 = 1 − 2 + 3 − 4 + 5 − … − 4 4 + 4 5 2 2 terms = 1 + 2 2 = 2 3
Consider n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ⌊ 5 3 n ⌋ ] , n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ⌊ 5 3 n ⌋ ] = 1 2 4 × 0 + 1 − 1 + … 1 2 5 terms − 2 + 2 − … 1 2 5 terms + … − 8 + 8 − … 1 2 5 terms 1 0 0 0 terms + 9 − 9 + … + 9 2 9 terms = 1 − 2 + 3 − 4 + 5 − 6 + 7 − 8 + 9 = 5
Consider n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ⌊ 5 4 n ⌋ ] , n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ⌊ 5 4 n ⌋ ] = 6 2 4 × 0 + 1 − 1 + … + 1 5 2 9 terms = 1
Therefore, n = 1 ∑ 1 1 5 3 [ k n × ( − 1 ) n + 1 ] = n = 1 ∑ 1 1 5 3 [ ( − 1 ) n + 1 ( ⌊ 5 n ⌋ + ⌊ 5 2 n ⌋ + ⌊ 5 3 n ⌋ + ⌊ 5 4 n ⌋ ) ] = 1 1 5 + 2 3 + 5 + 1 = 1 4 4